STRATEGI PENGEMBANGAN OBJEK WISATA KOLAM AIR PANAS NEGERI TULEHU KABUPATEN MALUKU TENGAH - Anthoneta Telsy Waelauruw; Gilbert Alvin Rumalatu (P3M Politeknik Negeri Ambon, 2023)
This study aims to develop a Tourism Object Development Strategy for the Hot Springs of Tulehu State, Central Maluku Regency. This research uses descriptive qualitative research with survey methods. Collecting data using observation, interviews and questionnaires. With the SWOT analysis technique, namely Strengths, Weaknes, Opportunities, Threats. The results of the study show that Tulehu has strengths in terms of exploiting existing natural resources, namely the Tulehu Hot Springs Tourism Object. While the weaknesses are in terms of inadequate infrastructure, lack of budget and the condition of human resources who are inexperienced managers for increasing the Tulehu State Hot Springs Tourism Object. The opportunity for the Tulehu State Hot Springs Tourism Object is to open jobs for the surrounding community. The lack of facilities and infrastructure is a threat so that it affects visiting tourists and the surrounding community will lose jobs. The suggestions for this research are: (1) Utilizing natural resources optimally, (2) Submitting a budget and working with the Department of Tourism, Youth and Sports, (3) Providing jobs for the community around the Tulehu National Hot Springs Tourism Object, (4) Improving Facilities that are not optimal. Keywords: Strategy, Tourism Object